PENGARUH KEPRIBADIAN DAN SITUASI TERHADAP PEMILIHAN MAKANAN PADA MAHASISWA TINGKAT PERTAMA - Purnamawati, Mutiara; Yuliati, Lilik Noor (Jurnal Ilmu Keluarga dan Konsumen, 2016)
This study aims to: (1) identify the habits of vegetable consumption among the first grade students before and after entering the dormitory; (2) analyze the personality, situation, and the food choices based on gender; and (3) analyze the factors that influence the food choices among the first grade students. This study included 288 students in the first grade (121 male students and 167 female students) that selected by cluster random sampling. Data were collected by self-administered methods. Variables measured consist of characteristic samples (allowance, age, and gender), vegetable consumption habits, personality (neuroticism, extraversion, openness to experience, agreeableness, and conscientiousness), the situation (places to eat), and the food choices (vegetables). This study found that personality (extraversion, openness to experience, and agreeableness) and situations (eating at home) had a positive influence on the food choices (vegetables). This means that the sample which had good socialize (extraversion), creative and imaginative (openness to experience), friendly and environmentally sensitive (agreeableness) would increase the choose to eat vegetables. Moreover, sample more ate vegetables when they were at home.